2018
DOI: 10.1186/s13045-018-0685-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of adverse events associated with bosutinib treatment of chronic-phase chronic myeloid leukemia: expert panel review

Abstract: Bosutinib, a BCR-ABL1 tyrosine kinase inhibitor (TKI), has been available for several years as a treatment for chronic-, accelerated-, and blast-phase chronic myeloid leukemia (CML), for patients with resistance or intolerance to prior therapy. In 2017, the BFORE trial demonstrated efficacy of bosutinib as first-line treatment in adult patients with newly diagnosed chronic-phase chronic myeloid leukemia (CP-CML). The most common adverse events (AEs) of any grade in bosutinib-treated patients in BFORE were diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…After switching from IM to NILO, the total number of ADEs decreased in most cases. Although new ADEs developed initially after switching to NILO, tolerance was acquired by management of ADEs [3,15]. In particular, fluid retention, digestive symptoms, and muscle symptoms including facial edema, peripheral edema, lids edema, general fatigue, depression, nausea, muscle pain and muscle cramps induced by IM were reduced significantly ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After switching from IM to NILO, the total number of ADEs decreased in most cases. Although new ADEs developed initially after switching to NILO, tolerance was acquired by management of ADEs [3,15]. In particular, fluid retention, digestive symptoms, and muscle symptoms including facial edema, peripheral edema, lids edema, general fatigue, depression, nausea, muscle pain and muscle cramps induced by IM were reduced significantly ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results might be due to the difference in drug adherence between the TKI groups. It has been reported that the Morisky high adherence was positively associated with complete hematologic remission in the chronic phase of CML [15,20]. Drug adherence has been reported as a critical factor for achieving molecular response in patients with CML [4][5][6][7], and non-adherence to TKI therapy may influence the disease outcome [5].…”
Section: Discussionmentioning
confidence: 99%
“…After switching from IM to NILO, the total number of ADEs decreased in most cases. Although new ADEs developed initially after switching to NILO, tolerance was acquired by management of ADEs [3,16]. In particular, fluid retention, digestive symptoms, and muscle symptoms including facial edema, peripheral edema, lids edema, general fatigue, depression, nausea, muscle pain and muscle cramps induced by IM were reduced significantly (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…These results might be due to the difference in drug adherence between the TKI groups. It has been reported that the Morisky high adherence was positively associated with complete hematologic remission in the chronic phase of CML [16,21]. Drug adherence has been reported as a critical factor for achieving molecular response in patients with CML [4][5][6][7], and non-adherence to TKI therapy may influence the disease outcome [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of adults with relapsed /refractory (R/R) acute lymphoblastic leukemia (ALL) and non-Hodgkin lymphoma (NHL) is still very poor [1][2][3][4][5]. With the increasing use of next-generation sequencing (NGS) and molecular biomarkers, early diagnosis and targeted therapy become possible [6][7][8][9][10]. It appears that NGS-based minimal residue disease (MRD) monitoring may better predict MRD relapse and lead to earlier intervention [11].…”
Section: Introductionmentioning
confidence: 99%